DROPOUT OF SECONDARY SCHOOL STUDENTS AND NEED FOR COUNSELLING IN NIGERIAN SCHOOLS - OPARADURU, John Onyemauche (EBSU Journal of Social Sciences and Humanities, 2024)
Dropout rate of secondary school students in Nigerian schools is a significant concern that requires attention and intervention through counselling services. Research has shown that various factors contribute to student dropout, including social context, self-perceptions, school engagement, and academic achievement. Dropping out of school is not an impulsive action but rather a cumulative process influenced by these factors. The location of schools also plays a role in student academic performance and dropout rates. Understanding the impact of school location on dropout rates can help inform interventions and support systems for at-risk students. Furthermore, the views of school heads and teachers are crucial in understanding the reasons behind student dropout. The findings of this paper have implications for policy and practice in addressing dropout rates and implementing effective interventions. Additionally, substance use, such as marijuana, has been identified as a contributing factor to high school dropout rates. Substance use issues through counselling and prevention programs can help reduce dropout rates among secondary school students. Therefore, the dropout of secondary school students in Nigerian schools is a complex issue influenced by various factors. Counselling services should be employed to play crucial role in addressing these factors and providing support to at-risk students.